Effect of LLZO on the in situ polymerization of acrylate solid-state electrolytes on cathodes. Issue 12 (13th March 2023) - Xu, Kaiyun; Zhou, Xiaoyu; Ge, Menghan; Qiu, Ziwen; Mao, Ya; Wang, Hefeng; Qin, Yinping; Zhou, Jingjing; Liu, Yang; Guo, Bingkun
Abstract : The addition of ceramic fillers can weaken the interaction between different polymers and make organic and inorganic components contact directly, which inhibit the segregation of solid electrolyte components. Abstract : The comprehensive performance of the state-of-the-art solid-state electrolytes (SSEs) cannot match the requirements of commercial applications, and constructing an organic–inorganic composite electrolyte in situ on a porous electrode is an effective coping strategy. However, there are few studies focused on the influence of inorganic ceramics on the polymerization of multi-organic components. In this study, it was found that the addition of Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZO) weakens the interaction between different polymers and makes organic and inorganic components contact directly in the solid electrolyte. These suppress the segregation of components in the in situ polymerized composite SSE, leading to a decrease in the polymer crystallization and improvement of electrolyte properties such as electrochemical stability window and mechanical properties. The composite solid-state electrolyte can be in situ constructed on different porous electrodes, which can establish close contact with active material particles, showing an ionic conductivity 4.4 × 10 −5 S cm −1 at 25 °C, and afford the ternary cathode stability for 100 cycles.